Analiz rezul'tatov kardiorespiratornogo nagruzocnogo testirovanija sportsmenov-edinoborcev v 30-letnej retrospektive - Egorov, N. A.; Chikov, A. E.; Medvedev, D. S. (Vestnik sportivnoj nauki; Sports science bulletin, 2021)
Indicators of aerobic operability of 344 male athletes engaged in wrestling, obtained with the help of cardiorespiratory load testing are analyzed. Comparative analysis of the obtained results was carried out with similar data in a 30-year retrospective. The results obtained over the last 10 years differ from used standards developed in 1988. As a result of carried out studies scales intended for assessment of level of aerobic capabilities of wrestlers at peak of load and at the level of PANO were developed. Scales provide gradation on 7 qualitative levels (very high, high, above an average, average, below an average, low and very low) during peak of physical activity, and on 5 qualitative levels (high, above an average, average, below an average and low) at achievement of AT. The athletes` assignment to one of these levels is determined on the basis of values of 4 indicators of aerobic capabilities (O2 uptake, CO2 emission, oxygen pulse, heart rate) obtained from the results of cardiorespiratory load testing.